Synthesis of Carbide Lime Waste Derived Base Catalyst (KF/CLW-Fe3O4) for Methyl Ester Production: An Optimization Study - Lim H.H.; Pua F.L.; Othman R.; Taufiq-Yap Y.H.; Krishnan S.G. (Diponegoro University, 2023)
Analysis of variance (ANOVA); Carbides; Catalyst activity; Esters; Hydrated lime; Lime; Palm oil; Scanning electron microscopy; Signal to noise ratio; Taguchi methods; Temperature programmed desorption; Transesterification; Base catalyst; Carbide lime; KF/CLW-fe3O4; Methyl esters; Optimisations; Optimization studies; Solid base catalysts; Transesterification reaction; Transesterifications; Carbon dioxide